PEMANFAATAN LIMBAH SABUT KELAPA DAN EKSTRAK TAOGE SEBAGAI PUPUK ORGANIK CAIR (POC) UNTUK MENINGKATKAN PERTUMBUHAN TANAMAN CABAI - Mariaulfa Mustam (Journal Techno Entrepreneur Acta, 2020)
The large needs of the community for chili make chili a strategic commodity that needs special attention from the government. In the 2015-2019 National Medium- Term Development Plan (RPJMN) for Food and Agriculture, chili is included as one of the 8 main food commodities along with rice, corn, soybeans, sugar, beef, shallots and oil palm. This shows that chili is a commodity that has an important role in national development planning. In 2013, chili was ranked fifth as the biggest contributor to inflation by 0.31 percent. This percentage rose to 0.43 percent in 2014. Chili also ranks fourth as the largest contributor to inflation nationally. Based on BPS data, national chili production continues to increase every year. In 2010, chili production reached 1.33 million tons. The analytical method that will be carried out is fermentation of coconut coir waste and bean sprout extract using Effective Microorganism 4 (EM4) for 14 days and testing of potassium levels with Atomic Absorption Spectrophotometer (AAS), FTIR test, as well as the application of chili seeds with variations of POC 1ml, 3ml , 5ml, 10ml, 15ml, 20ml, data processing, data analysis, reporting and publication of Output Types in the form of prototypes. Status / Identity Outcome Outcome: Product registered as a Simple Patent with No. Application for S15201909925. The additional output is the National Journal Not Accredited with the name of the journal "Journal of Science and Technology Makassar UTS" Number ISSN: 2633-2294 with the status "Accepted". The proposed research TKT namely The concepts and important characteristics of a technology have been proven analytically and experimentally. The research results obtained are a good 10ml POC volume for chilli plants and the resulting Potassium content 169,771mg / kg (ppm).